Trends in vegetation cover changes in Bonny area of the Niger Delta - A Adoki (Journal of Applied Sciences and Environmental Management)
The main vegetation type in the area is the mangrove forest, which occupies most of the Niger Delta. The other vegetation type is the secondary (re-growth) vegetation that occupies a small area. The secondary vegetation is surrounded by the mangrove swamp forest; a two-layered vegetation. The one–layered forest has mangrove trees of 3-14 m high without undergrowth forming the only layer while the two-layered forest has a top layer made up of Rhizophora species (3-32 m high) depending on the height of trees at each site and a ground layer composed mainly of the fern Acrostichum aureum and seedlings of the tree species. There is a dearth of epiphytic bryophytes and lichens on the boles and branches of the trees. From satellite imageries of the area, it is evident that the landcover classes changed across the three epochs. The water class covered an area of 111.91km2 in 1986, 108.90km2 in 1998 and 103.41km2 in 2007. Mature forest (Forest I) occupies a total area of 85.64km2 in 1986; decreased significantly to 59.68km2 in 1998 and 59.30km2 in 2007. This could be attributed to man-made and industrial activities. Secondary Forest (Forest II) covered 11.18km2 in 1986, but increased to 43.49km2 in 1998 and decreased to 23.30km2 in 2007. Urban/Industrial/Sand class had a steady increase across the epochs. This class which covered about 10.37km2 in 1986 increased to 14.73km2 in 1998, and 25.28km2 in 2007. This increment is attributed to influx of humans into the area as a result of increase in Oil and Gas industry activities. Mangrove class covered 87.02km2 in 1986 but increased to 95.86km2 in 1998 and 106.79km2 in 2007. Stressed Vegetation occupied 16.38km2 in 1986; this class type was only evident during that period. Sparse vegetation which covered an area of 5.23km in 1986; decreased slightly to 5.07km2 in 1998 but increased to 9.07 km2 in 2007. Overall, the most dramatic change recorded is with respect to the areal extent of Urban/Industrial/Sand which increased by about 42% between 1986 and 1998 and about 144% between 1986 and 2007. The area covered by mangrove forest consistently declined over all the epochs while the reverse was the case with respect to the area covered by sparse vegetation. The area covered by stressed vegetation in 1986 disappeared during other epochs.